Regenerative medicine applications in organ transplantation - Orlando, Giuseppe 1970- (Elsevier/AP, 2014)
Regenerative Medicine Applications in Organ Transplantation illustrates exactly how these two fields are coming together and can benefit one another. It discusses technologies being developed, methods being implemented, and which of these are the most promising. The text encompasses tissue engineering, biomaterial sciences, stem cell biology, and developmental biology, all from a transplant perspective. Organ systems considered include liver, renal, intestinal, pancreatic, and more.